The piety of learning : Islamic studies in honor of Stefan Reichmuth - Reichmuth, Stefan; Kemper, Michael; Elger, Ralf (Islamic history and civilization ;, 2017)
The Piety of Learning' testifies to the strong links between religious and secular scholarship in Islam, and reaffirms the role of philology for understanding Muslim societies both past and present. Senior scholars discuss Islamic teaching philosophies since the 18th century in Nigeria, Egypt, the Ottoman Empire, Central Asia, Russia, and Germany. Particular attention is paid to the power of Islamic poetry and to networks and practices of the Tijaniyya, Rifa?iyya, Khalwatiyya, Naqshbandiyya, and Shadhiliyya Sufi brotherhoods. The final section highlights some unusual European encounters with Islam, and features a German Pietist who traveled through the Ottoman Empire, a Habsburg officer who converted to Islam in Bosnia, a Dutch colonial Islamologist who befriended a Salafi from Jeddah, and a Soviet historian who preserved Islamic manuscripts.